2022
DOI: 10.21203/rs.3.rs-1667539/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does customised care improve satisfaction and positively enable parents in sustained home visiting for mothers and children experiencing adversity?

Abstract: Background The Maternal Early Childhood Sustained Home-visiting program (MECSH) is a structured nurse-delivered program designed to address health inequities experienced by families experiencing significant adversity. There is strong evidence for the effectiveness of this program, but limited research exploring the practice and process elements that are core to positive parent outcomes. This study aimed to examine the relationship between customised care related to the mother’s risk factors and parent satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A previous study (Kanda et al, 2022b) found that home-visiting nurses were actively engaged in ensuring the care they provided had high fidelity to the programme in terms of scheduled content but also engaged in adaptation and customization of the care based on maternal risks. Furthermore, mothers who were provided with customized care in response to their risks had a higher level of satisfaction with the care provided and a sense of enablement (Kanda et al, 2022a). It is clear that well-trained nurses have high levels of competency in creating variations of care whilst remaining true to the core elements of an evidence-based programme.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…A previous study (Kanda et al, 2022b) found that home-visiting nurses were actively engaged in ensuring the care they provided had high fidelity to the programme in terms of scheduled content but also engaged in adaptation and customization of the care based on maternal risks. Furthermore, mothers who were provided with customized care in response to their risks had a higher level of satisfaction with the care provided and a sense of enablement (Kanda et al, 2022a). It is clear that well-trained nurses have high levels of competency in creating variations of care whilst remaining true to the core elements of an evidence-based programme.…”
Section: Backg Rou N Dmentioning
confidence: 99%